DE LA APLICACIÓN DE LOS PROCEDIMIENTOS PENALES A LAS CONTRAVENCIONES ECONÓMICAS - Díaz Perdomo, Julio Cesar (Revistas ICDP, 2026)
DE LA APLICACIÓN DE LOS PROCEDIMIENTOS PENALES A LAS CONTRAVENCIONES ECONÓMICAS